The Influence of Gendered Access/ Control of Land and Dairy Products on Household Welfare in Murang’a County, Kenya - Mwangi, Judy Wambui; Kimani, Elishiba Njambi; Masiga, Casper Operee (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 2 (2020): Journal of Advanced Research in Humanities and Social Science, 2020)
Studies have revealed that there is existing gender inequality in access and control of resources, benefits and opportunities in the society including agricultural resources and benefits. This informed the concern of this study which sought to investigate the influence of the gendered access and control of land and dairy products on household welfare. The study was done in Murang’a County-Kenya. The study was guided by the Marxist feminism theory advanced by Friedrich Engels. It adopted a cross-sectional research design. A purposive sampling technique was used to select Kigumo out of the seven Sub-counties in Murang’a County as the study area. Further, a simple random sampling technique was used to select a total of four hundred and forty-two (442) male and female headed households practicing dairy farming in the Sub-county as the respondents of the study. The community leaders and key county officers were also included as key informants. To collect the data, the study used interview schedules for the selected household heads, guided questionnaires for the key informants and an observation checklist. Qualitative data was analyzed on the basis of themes derived from the study objective while quantitative data was analyzed using SPSS. The household welfare was gauged on the basis of the parameters drawn from the Constitution of Kenya (2010) Article 43 on social and economic rights namely health, housing, food, water and education. The study established that gendered access and control of land and dairy products has a major influence on the provision of household welfare. How to cite this article: Mwangi JW, Kimani EN, Masiga CO. The Influence of Gendered Access/ Control of Land and Dairy Products on Household Welfare in Murang’a County, Kenya. J Adv Res Humani Social Sci 2020; 7(2): 20-26.